Social norms theory and exercise, nutrition, and sexual behaviors and their relationship to perception of health in female and male college students - Buchanan, Christina, author; Davies, Timothy G., advisor (Colorado State University. Libraries, 2008)
The purpose of this study was to examine Colorado State University students' exercise, nutrition, weight management, and sexual behaviors that may enhance disease prevention and those behaviors' relationship to students' perceived health. A secondary purpose of this research was to examine how students' perceptions of their peers' sexual behaviors influenced their own sexual behaviors based on social norms theory (SN). The instrument used was the American College Health Association-National College Health Assessment (ACHA-NCHA). The subjects were female and male college students 18-25 years old, N = 2890. Data analysis: descriptive statistics, Pearson's r, Spearman rho, ANOVA, and Mann Whitney U tests were used. Results: 42.4% did not meet current exercise recommendations, 94.3% did not eat 5 fruits and vegetables (FV) per day, 61.4% of females and 23.1% of males were trying to lose weight, 77.1% of females and 65.1 of males were at the desired weight (BMI), 25.9% never used condoms, 35.0% always used condoms, 27.1% had 0 sexual partners (SP) in the past year, 1.3% thought the typical student had 0 SP, 10.7% had vaginal intercourse (VI) 1-2 times in the past month versus 27.6% that thought the typical student had VI 1-2 times. Correlations and ANOVAS: perceived health (PH); and exercise, FV, and BMI were significantly correlated (p < 0.01). Exercise, FV, weight management (WM), and BMI were significantly different between females and males. There were no significant correlations between PH and sexual behaviors (condom use (C), SP, VI). Typical student condom use (TC), typical student SP (TSP), VI, and typical student VI (TVI) were significantly different between females and males. SN and sexual behavior: SP and TSP; and VI and TVI were significantly correlated (p < 0.01), C and typical student condom use were not significant. Conclusions: this sample of students took exercise, nutrition, WM, and BMI into account when self-assessing their health (PH). Students did not take sexual behaviors into account when self-assessing their health. Students seemed to be influenced by their perception of their peers' behavior with regard to sexual behaviors, according to social norms theory. Females and males differ in health practices and perceptions.
Keywords: college students; exercise; nutrition; social norms; weight management; public health; health education